The Influence Of Principal Leadership Management On Teacher Self-Efficacy Through Teacher Learning Innovation At SMAN 1 Utan, Sumbawa Regency - Abdullah; Osijo, Immanuel Ustradi; Yustiana, Dewi; Uripan, Koen Irianto; Sutomo (International Humanity Advance, Business & Sciences, 2026)
This study aims to analyze the influence of principals' leadership management on teacher self-efficacy through teacher learning innovations at SMAN 1 Utan, Sumbawa Regency. In particular, this study aims to: (1) determine the influence of principal leadership management on teacher learning innovation; (2) determine the influence of teacher learning innovations on teacher self-efficacy; and (3) determine the influence of principal leadership management on teacher self-efficacy through teacher learning innovations. The population in this study is all teachers of SMAN 1 Utan, Sumbawa Regency, which is 45 people. Because the population is relatively small, this study uses the census method, where the entire population is used as a research sample, with the criterion of teachers who have worked for more than one year. This type of research uses a quantitative approach with data analysis using Partial Least Squares (PLS), which is processed with the help of SmartPLS 3.0 software. The results of the study showed that: (1) the principal's leadership management had a significant effect on teacher learning innovation at SMAN 1 Utan, Sumbawa Regency; (2) teacher learning innovations have a significant effect on teacher self-efficacy; and (3) Principal leadership management has a significant effect on teacher self-efficacy through teacher learning innovation. These findings show that effective principal leadership is able to create a work environment that supports innovation, increases teachers' creativity in learning, and strengthens teachers' confidence in their professional abilities. Thus, strengthening the principal's leadership management and increasing learning innovation are key factors in building confident, adaptive, and high-performing teachers.